THE EFFECTIVENESS OF A TEACHING STRATEGY BASED ON THE PERKINS AND BLYTHE MODEL IN ACQUIRING BIOLOGICAL CONCEPTS AND SCIENTIFIC VALUES AMONG ELEVENTH GRADE SCIENTIFIC STUDENTS - Zuher Ahmed Ali (SocioEdu: Sociological Education, 2025)
This study aimed to investigate the effectiveness of a teaching strategy based on the Perkins and Blythe model in acquiring biological concepts and developing scientific values among eleventh-grade scientific students. The researcher employed a quasi-experimental methodology with partial control design on a sample of 69 students deliberately selected from eleventh-grade students at Zakho Preparatory School for Boys for the academic year 2024-2025. The sample was randomly distributed into two groups: an experimental group consisting of 33 students who studied using the Perkins and Blythe model-based teaching strategy, and a control group consisting of 36 students who studied according to the traditional method. After ensuring equivalence across several variables, the researcher determined the scientific material for the first unit, which represents the first three chapters of the eleventh-grade biology textbook (Internal Balance and Transport, Photosynthesis, Cellular Respiration). To verify the research objectives, the researcher prepared 24 actual lesson plans for each group, and developed a biological concepts acquisition test consisting of 30 questions in its final form, and adopted the scientific values scale prepared by Al-Mohtaseb (2018) consisting of 45 items distributed across 8 domains with both positive and negative items. After verifying validity and reliability indicators for the test items and scientific values scale, data were analyzed using the t-test for two independent samples. Results showed a statistically significant difference between the mean scores of students in the experimental and control groups on both the biological concepts acquisition test and the scientific values scale in favor of the experimental group. Based on the findings, the researcher made several recommendations and suggestions for future research studies.